On madness without words: gestures in Homer’s poems as a nonverbal means of depicting madness - Chruściak, Ilona (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2013)
The paper discusses various ways of depicting madness in Homer’s epics based on the example of a scene from the Iliad, in which Andromache is compared to a maenad, as well as the scene concerning the feast of suitors in book XX of the Odyssey. Depicting madness by means of gestures affects the reception of the described scenes by the external and internal epic audience in a very special way. The gestures that are described invoke in the listeners associations related to their own experiences and appeal to particular emotions, whose presence affects the reception of an epic. The gestures and the nonverbal message allude to the Bacchic trance and this raises the question whether Homer and his audience were familiar with the cult of Dionysus.